Effect of ATG‐F on B‐cell reconstitution after hematopoietic stem cell transplantation. (13th March 2015) - Roll, Petra; Muhammad, Khalid; Stuhler, Gernot; Grigoleit, Ulrich; Einsele, Hermann; Tony, Hans‐Peter
Abstract: Antithymocyte globulin Fresenius (ATG‐F) is used before hematopoietic stem cell transplantation to prevent graft rejection and graft‐versus‐host disease in patients with HLA‐matched unrelated donors or mismatched volunteers. However, little is known about the effect of ATG‐F on the reconstitution of B‐cell subsets. Sixty‐seven patients were longitudinally studied at day 15, day 30, and then monthly after hematopoietic stem cell transplantation. Conditioning regimes included ATG‐F, which was infused at days 3, 2 and 1 at a dosage of 10 mg/kg/d. Twenty‐seven patients received conditioning regimes without ATG. ATG‐treated patients showed a significant delay of CD19+ B cells in the early recovery period. The absolute numbers of circulating CD19+ B cells were significantly lower ( P < 0.05) up to 5 months post‐transplantation compared to non‐ATG patients. The recovery of the memory compartment was delayed in both groups and did not reach normal values 1‐year post‐transplantation. ATG‐treated patient showed significantly lower absolute numbers of circulating CD27+ memory B cells in the first‐month after transplantation compared to non‐ATG patients. In conclusion, treatment with ATG in the conditioning regime of patients undergoing allogeneic hematopoietic stem cell transplantation leads to a significant delay of CD19+ B cells. Thus, ATG seems also to negatively influence B‐cell immune reconstitution.